The integrin coactivator Kindlin-2 plays a critical role in angiogenesis in mice and zebrafish - Pluskota, Elzbieta (American Society of Hematology, 2011)
Kindlin-2, a widely distributed cytoskeletal protein, has been implicated in integrin activation, and its absence is embryonically lethal in mice and causes severe developmental defects in zebrafish. Knockdown of kindlin-2 levels in endothelial cells resulted in defective adhesive and migratory responses, suggesting that angiogenesis might be aberrant even with partial reduction of kindlin-2. This hypothesis has now been tested in the kindlin-2(+/−) mice. RM1 prostate tumors grown in kindlin-2(+/−) mice had fewer blood vessels, which were thinner and shorter and supported less tumor growth compared with wild-type littermates. The vessels that did form in the kindlin-2(+/−) mice lacked smooth muscle cells and pericytes and had thinner basement membranes, indicative of immature vessels. VEGF-induced angiogenesis in matrigel implants was also abnormal in the kindlin-2(+/−) mice. Vessels in the kindlin-2(+/−) mice were leaky, and BM transplantation from kindlin-2(+/−) to WT mice did not correct this defect. Endothelial cells derived from kindlin-2(+/−) mice had integrin expression levels similar to WT mice but reduced αVβ3-dependent signaling, migration, adhesion, spreading, and tube formation. Developmental angiogenesis was markedly impaired by kindlin-2 morpholinos in zebrafish. Taken together, kindlin-2 plays an important role in pathologic and developmental angiogenesis, which arises from defective activation of integrin αVβ3.